KEPATUHAN WAJIB PAJAK DITINJAU DARI KESADARAN WAJIB PAJAK DAN PEMAHAMAN PERPAJAKAN (Studi Kasus pada Pendidik dan Tenaga Kependidikan (Tendik) Sekolah Dasar) - Rika Monika, Ina Khodijah, Mochamad Fahru Komarudin (Integrative Perspectives of Social and Science Journal, 2025)
The Influence of Taxpayer Awareness and Tax Understanding on Taxpayer Compliance (Case Study of Elementary School Educators and Education Personnel). This study was conducted to examine the extent to which taxpayer awareness and the level of tax understanding influence taxpayer compliance in Elementary School Educators and Education Personnel. The approach used is a quantitative method with data collection techniques using questionnaires. The number of samples in this study was 100 respondents. Data analysis was carried out using classical assumption tests and linear regression analysis. The results of the t-test showed that taxpayer awareness had a significant effect on taxpayer compliance with the results of t count> t table (5.272> 1.660). And tax understanding with the results of t count < t table (3.432<1.660). So tax understanding also has an effect on taxpayer compliance. For the F count value from the test results showed the F count> F table (57.084>56.441). This means that both variables, namely taxpayer awareness and tax understanding simultaneously influence taxpayer compliance. The conclusion of this study is that it can be concluded that both partially and simultaneously the variables of taxpayer awareness (X1) and tax understanding (X2) have an influence on taxpayer compliance (Y) among Elementary School Educators and Teaching Staff (Tendik).